The introduction the European approach to waste classification in Ukraine - Жуковський, Тимофій Федорович; Ткачова, Олена Володимирівна; Пшенічнова, Олена Леонідівна; Карцев, Валерій Геннадійович; Котелевець, Марина Михайлівна; Соколова, Олена Ігорівна (Technology audit and production reserves, 2016)
One of the areas of implementation of European legislation on waste in Ukraine is the European approach and the application of the principles of waste classification. The object of study is European Union legislation and applicable legal acts of Ukraine regarding the classification of waste. The comparative analysis of the current Ukrainian and European legislation on waste showed a significant difference in the principles and approaches of waste classification. In National legislation waste is classified by the State Waste Classifier DK 005-96, where waste is no gradation in the degree of danger to the environment and human health. The legislation of the European Union developed a List of waste where the wastes are classified as dangerous or safe, and which is mandatory for use by all Member States. To introduce in Ukraine European approach to waste classification at the State Waste Classifier DK 005-96 was set up national lists of waste, harmonized with the European List of Waste. Using Lists it can be classified as waste produced in Ukraine, determine their affiliation to the safe or dangerous, and develop environmentally safe ways of waste treatment. Waste classification by developed Lists will introduce internationally comparable data for environmental monitoring programs, and high-quality consistent statistics on waste generation and management.